What Drives Them to Drive?—Parents' Reasons for Choosing the Car to Take Their Children to School - Westman, Jessica; Friman, Margareta; Olsson, Lars E. (Frontiers in Psychology, 2017)
Children’s school journeys have changed vastly during recent decades: More children are being driven to school in private cars instead of walking and cycling, with many who are entitled to a free school bus service still being driven. Earlier research into travel mode choice has often investigated how urban form impacts upon mode choice regarding school journeys – in particular how urban form hinders or enables the use of the active mode. This paper quantitatively explores parents’ stated reasons for choosing the car and the relationship between these reasons and the decision to use the car to take their children to school. We additionally investigate the relationship between sociodemographic factors, distance, and both the stated reasons and the actual mode decision. A sample of 245 parents (194 women) of school children aged 10-15 in the County of Värmland in Sweden were included in the study. The results of PLS-SEM show that the factor Social convenience has a direct relationship with the frequency of car use indicating that the wish to accompany the child and the convenience of car impacts on car choice. If the child is not allowed to travel independently, the parents choose the car to take him/her to school. Sociodemographic factors had a direct relationship with the stated reasons, whereby parents with a higher level of education valued safety/security less. Quite surprisingly, distance (i.e. environmental factor) did not affect car use, indicating that parents drive their children to school regardless of distance. By isolating the particular reasons for choosing the car, this paper focuses on a potentially important missing piece as regards finding out what motivates the increasing car usage in children’s school journeys. An increased knowledge of what motivates the decision to take children by car is important for effective policies aimed at changing parents’ inclination towards choosing the car.